Axonal chemokine-like Orion induces astrocyte infiltration and engulfment during mushroom body neuronal remodeling - Ana Boulanger (Nature Portfolio, 2021)
Astrocytes can engulf axonal debris in the developing brain. However, the mechanisms regulating astrocyte recruitment to the proper axons is unclear. Here, the authors identify Orion as a signal for astrocyte infiltration and engulfment to the mushroom bodies in the Drosophila developing brain.